Squamous cell carcinoma with sarcomatous transformation of the penis - Joana dos Santos; Rafael Cabrebra; Beatriz Neves; Eduardo Silva; António Polónia (University of São Paulo, 2021)
Malignant tumors of the penis are rare, most of them being squamous cell carcinomas (SCCs). We report the case of a 75-year-old man with a large penile mass submitted to partial penectomy. The specimen showed an exophytic mass involving the glans, coronal sulcus, and prepuce. Microscopic examination showed a carcinoma with two distinct areas: a mixed SCC and a sarcomatoid carcinoma. The SCC component had areas of verrucous carcinoma and areas of classical invasive SCC. The tumor cells expressed p63 with the absence of p16 expression. Vimentin and p53 were positive in the sarcomatous component. The morphology and immunohistochemistry were compatible with mixed SCC (verrucous hybrid-sarcomatoid carcinoma). Additionally, the tumor cells also expressed 3 different clones of PDL1 (22C3, SP263, and SP142). Two months later, the patient presented local recurrence with multiple lymph nodes and lung metastases, dying 7 weeks later. Mixed tumors represent diagnostic challenges. The correct identification of adverse prognostic factors can be the first step to implement the treatment with a higher probability of success.